2023
DOI: 10.1177/2057150x221146646
|View full text |Cite
|
Sign up to set email alerts
|

Equity versus efficiency: A spatial analysis of residential aged care resources in Beijing

Abstract: Based on data collected from residential aged care facility websites and the Sixth China National Population Census, this paper studies the spatial pattern of Beijing's aged care resources in the framework of spatial location of public facilities. The results show that at the township/street level, the overall distribution of public aged care resources is relatively balanced, showing positive spatial autocorrelation, while private aged care resources show partially negative spatial autocorrelation. Spatial reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Meanwhile, the allocation of public service facilities is one of the criteria for measuring community governance performance. In the existing assessment system, the coverage of public services and allocation of public facility resources are important measurement indicators (Bi and Li, 2020; Ma et al, 2016). Therefore, to a large extent, the number of public services and facilities in the community determines the level of community governance performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, the allocation of public service facilities is one of the criteria for measuring community governance performance. In the existing assessment system, the coverage of public services and allocation of public facility resources are important measurement indicators (Bi and Li, 2020; Ma et al, 2016). Therefore, to a large extent, the number of public services and facilities in the community determines the level of community governance performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the role of people in social space, Bofulin pointed out that the flow and aggregation of people are the foundation for the formation and change of social-spatial differentiation [14]. Kidokoro found that the degree of gentrification and differentiation in the Tokyo worker community is highly autocorrelated in local space [15]; Huang found a significant correlation between the population and the type of residential space [16]; Qiang found that the number of social areas formed by migrant workers in cities is stable, their internal attributes are constantly changing, and social-spatial differentiation tends to be clear and concentrated [17]; Sheng found that there is a significant differentiation in the spatial distribution of employment and housing among graduates from low-income universities in Beijing [18]; Bi found that the working and living space and registered residence of the population are closely related to the distribution of primary and secondary schools [19]. As the connotation of social space expands to include the space where residents' daily behaviors involve, stay, and feel, research has begun to focus on the social space and specific behaviors of specific populations [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eldercare institutions, as public facilities, have their spatial distribution rooted in political-economic contexts and social processes. They are highly correlated with regional population density and socioeconomic factors (Dear, 1978;Bi et al, 2020). Niefeld (2005) and Ryvicker at al., (2012) further propose that barriers to the use of eldercare resources are more attributable to geographic constraints and information access barriers rather than economic restrictions.…”
Section: Introductionmentioning
confidence: 97%